2020
DOI: 10.1186/s12884-020-03301-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing factors associated with poor maternal mental health among mothers of children born small and sick at 24–47 months in rural Rwanda

Abstract: Background Global investments in neonatal survival have resulted in a growing number of children with morbidities surviving and requiring ongoing care. Little is known about the caregivers of these children in low- and middle-income countries, including maternal mental health which can further negatively impact child health and development outcomes. We aimed to assess the prevalence and factors associated with poor maternal mental health in mothers of children born preterm, low birthweight (LBW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…We found a high burden of maternal CMDs in Zimbabwe in our study population (29.5%). This nding is in keeping with a study conducted in two rural districts in Zimbabwe which reported maternal depression prevalence of 21% in Chipinge and 34% in Mutasa district (18) .Much higher prevalence of maternal mental health outcomes were reported in studies conducted in Rwanda (51.6%), and Nigeria (40.7%) (25,32). However, the high prevalence in these reviewed studies may be attributed to selection bias as a result of interviewing inpatients, health facility clients, and mothers of children with known morbidity as well as a difference in the validity and speci city of the tools used in assessing for the maternal CMDs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found a high burden of maternal CMDs in Zimbabwe in our study population (29.5%). This nding is in keeping with a study conducted in two rural districts in Zimbabwe which reported maternal depression prevalence of 21% in Chipinge and 34% in Mutasa district (18) .Much higher prevalence of maternal mental health outcomes were reported in studies conducted in Rwanda (51.6%), and Nigeria (40.7%) (25,32). However, the high prevalence in these reviewed studies may be attributed to selection bias as a result of interviewing inpatients, health facility clients, and mothers of children with known morbidity as well as a difference in the validity and speci city of the tools used in assessing for the maternal CMDs.…”
Section: Discussionsupporting
confidence: 87%
“…This is further strengthened by our nding whereby CMD were signi cantly higher among mothers of children who experienced frequent appetite loss. In contrast a study conducted in USA found mothers presenting with common mental disorders to more likely have overweight children attributing such to poor watching of diet and children being exposed to more takeaway as opposed to home cooked meals (37) The presence of a partner was associated with a decreased odds of maternal CMDs, with one study arguing that this is because spousal support generates a better life satisfaction which in turn improves maternal health outcomes (32). A study in Sub-Saharan Africa that assessed the effect of spousal support on maternal burnout, depression and anxiety reported that perceived spousal support reduced both burnout and depression (38).…”
Section: Discussionmentioning
confidence: 95%
“…This might be due to women with low socioeconomic status may face difficulties to fulfill their needs and newborns during the postpartum period. Low socioeconomic status has been connected with a high rate of different mental health problems [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feeding difficulties among children with disabilities are associated with high rates of malnutrition and early life mortality [45]. Previous studies conducted in Rwanda among children born small and sick reported high rates of potential disabilities at ages 2 to 4 years [46] and higher rates of malnutrition among children with feeding difficulties [47], thus additional specialized nutrition interventions are likely required to address these children's needs. Based on this challenge, in 2019, the PDC program integrated early intervention using the Baby Ubuntu model [48], a group participatory early intervention program starting from 6 months for young children with disability and their families.…”
Section: Plos Onementioning
confidence: 99%